2008
DOI: 10.1111/j.1471-0528.2008.01904.x
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture as an adjunct to standard treatment for pelvic girdle pain in pregnant women: randomised double‐blinded controlled trial comparing acupuncture with non‐penetrating sham acupuncture

Abstract: Objective To investigate whether acupuncture has a greater treatment effect than non-penetrating sham acupuncture in women with pelvic girdle pain (PGP) during pregnancy.Design Randomised double-blinded controlled trial.Setting East Hospital, Gothenburg, and 25 antenatal primary care units in the region of Västra Götaland, Sweden.Population A total of 115 pregnant women with a clinical diagnosis of PGP who scored ‡50 on a 100-mm visual analogue scale (VAS).Method Women were randomly allocated to standard treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
134
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(144 citation statements)
references
References 55 publications
3
134
0
7
Order By: Relevance
“…[28][29][30][31][32][33] To date, two rigorously conducted systematic reviews have been published. 7,34 The first of these was a Cochrane Review of eight studies (1305 participants) testing the effects of adding various pregnancy-specific exercises, physiotherapy, acupuncture and pillows to standard pre-natal care.…”
Section: Acupuncturementioning
confidence: 99%
“…[28][29][30][31][32][33] To date, two rigorously conducted systematic reviews have been published. 7,34 The first of these was a Cochrane Review of eight studies (1305 participants) testing the effects of adding various pregnancy-specific exercises, physiotherapy, acupuncture and pillows to standard pre-natal care.…”
Section: Acupuncturementioning
confidence: 99%
“…Also, the complaint is often trivialized in healthcare [14,15] . Efficient treatments are lacking, but acupuncture and specific stabilising exercises as an adjunct to a pelvic belt, ergonomic advice and home training exercises have been shown to decrease pain and improve function [2,11,16] . PGP has been found to disappear soon after delivery but tends to recur in future pregnancies [7] .…”
mentioning
confidence: 99%
“…PGP causes dysfunction, emotional distress [10] , and reduced health-related quality of life for the pregnant woman [8,9,11,12] . Qualitative studies have shown that PGP in pregnancy causes women, struggling with daily life, to doubt their roles and identities as professionals and mothers [12,13] .…”
mentioning
confidence: 99%
“…It was part of a project encompassing an RCT comparing CST plus ST with ST alone for well-defined PGP [10] . ST (education, a pelvic belt and home exercise) was the same as in two previous treatment studies for PGP [8,9] . CST was performed in a spacious room with windows and natural light.…”
Section: Methodsmentioning
confidence: 99%
“…out in Scandinavia [8][9][10][11][12] , the condition has also been reported in Africa [3] , the Americas [13] , Asia [14,15] , Australia [13] and Europe [16][17][18] . PGP is a musculoskeletal pain concentrated to an area between the posterior iliac crests and gluteal folds, particularly in the sacroiliac joint area.…”
mentioning
confidence: 99%